Internalisasi Nilai-Nilai Akhlak pada Mata Pelajaran PAI di SMP Panca Budi Medan - Arivia Raihanah Lubis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to explain how moral principles are assimilated in Islamic Religious Education (IRE) learning at SMP Panca Budi Medan. Internalization of moral ideals refers to efforts made to develop moral behavior consistent with Islamic beliefs. This is accomplished by the use of techniques such as example, practice, and direction. In this context, IRE subjects play a vital role in developing religious and responsible students. This study took a qualitative approach, with data gathered through 16 weeks of observation and conversation with educators. The study's findings indicate that a systematic learning strategy, which incorporates congregational prayer and reading the Koran before classes, is beneficial in raising pupils' moral consciousness. However, various issues exist, such as students' lack of awareness and a limited learning time. This research aims to improve character education in schools and serve as a resource for educators to properly implement moral ideals.